Taxing the Big Tech in the European Union - Zafiroski, Jovan; Neshovska Kjoseva, Elena (Springer Cham, 2023)
In order to ensure a fairer and more efficient tax world, international tax rules should be adapted to the globalization/regionalization of business and the digitalization of economic activities. In recent years, numbers of reform proposals were developed to address the tax challenges of the digital economy. Additionally, major tax scandals over the past few years have shown that it has never been easier for large multinationals to virtually locate their operations in jurisdictions where the corporate tax system is more favorable, even if companies still have physical stores, factories, or warehouses in other countries. Therefore, the tax question of the twenty-first century is not whether they pay taxes, but where they are paid. The tax challenges of the digitalized economy are global, and need global solutions. The introduced unilateral and country-specific tax measures fragment the European digital single market, increase competitive distortions, compliance burden and double taxation disputes. Therefore, a European solution is required for a problem that goes beyond national borders. But, is there any way toward European digital tax environment where tech giants would pay their fair share of taxes and contribute to national economies, for the benefit of all?
Keywords: Digitalization, Digital economy, Taxation, European Union, Digital service tax